PENGARUH e-LKPD BERBASIS PROBLEM BASED LEARNING BERBANTUAN APLIKASI LIVEWORKSHEET TERHADAP HASIL BELAJAR KOGNITIF DAN SIKAP TANGGUNG JAWAB PESERTA DIDIK PADA MATERI NORMA DALAM KEHIDUPANKU DI KELAS V - Murtiana; Osa Juarsa; Neza Agusdianita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of using Problem Based Learning (PBL)-based e-LKPD assisted by the Liveworksheet application on students’ cognitive learning outcomes and responsibility attitudes in the topic Norms in My Life for fifth-grade students at SDN 44 Bengkulu City, as well as to examine the relationship between cognitive learning outcomes and students’ responsibility attitudes. This study employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The research sample consisted of an experimental class that used PBL-based e-LKPD assisted by Liveworksheet and a control class that used conventional learning. Data collection techniques included cognitive learning outcome tests and responsibility attitude questionnaires. The data were analyzed using the Independent Sample t-test, N-Gain test, and Pearson correlation test. The results showed that the use of PBL-based e-LKPD assisted by Liveworksheet had a significant effect on students’ cognitive learning outcomes with a Sig. (2-tailed) value of 0.000 < 0.05 and a calculated t-value of 7.179. In addition, the use of PBL-based e-LKPD assisted by Liveworksheet also had a significant effect on students’ responsibility attitudes with a Sig. (2-tailed) value of 0.001 < 0.05 and a calculated t-value of 3.632. The correlation test results indicated a very strong and significant positive relationship between cognitive learning outcomes and students’ responsibility attitudes, with a Pearson Correlation value of 0.931. Therefore, the use of PBL-based e-LKPD assisted by Liveworksheet was effective in improving elementary school students’ cognitive learning outcomes and responsibility attitudes.